Q-learning based distributed denial of service detection - Hiba Salah Yaseen; Ahmed Al-Saadi (Institute of Advanced Engineering and Science, 2023)
Distributed denial of service (DDoS) attacks the target service providers by sending a huge amount of traffic to prevent legitimate users from getting the service. These attacks become more challenging in the software-defined network paradigm, due to the separation of the control plane from the data plane. Centralized software defined networks are more vulnerable to DDoS attacks that may cause the failure of all networks. In this work, a new approach is proposed based on q-learning to enhance the detection of DDoS attacks and reduce false positives and false negatives. The results of this work are compared with entropy detection in terms of the number of received packets to detect the attack and also the continuity of service for legitimate users. Moreover, these results indicate that the proposed system detects the DDoS attack from flash crowds and redirects the traffic to the edge of the data center. A second controller is used to redirect traffic to a honeypot server that works as a mirror server. This guarantees the continuity of service for both normal and suspected traffic until further analysis is done. The results indicate an increase of up to 50% in the throughput compared to other approaches.